An Assessment of the Oral Bioavailability of Three Ca‐Channel Blockers Using a Cassette‐Microdose Study: A New Strategy for Streamlining Oral Drug Development. Issue 9 (2nd June 2015) - Yamashita, Shinji; Kataoka, Makoto; Suzaki, Yuki; Imai, Hiromitsu; Morimoto, Takuya; Ohashi, Kyoichi; Inano, Akihiro; Togashi, Kazutaka; Mutaguchi, Kuninori; Sugiyama, Yuichi; Donovan, Maureen D.; Langguth, Peter; et al.
<x xml:space="preserve">Abstract</x> A cassette‐microdose (MD) clinical study was performed to demonstrate its usefulness for identifying the most promising compound for oral use. Three Ca‐channel blockers (nifedipine, nicardipine, and diltiazem) were chosen as model drugs. In the MD clinical study, a cassette‐dose method was employed in which three model drugs were administered simultaneously. Both intravenous (i.v.) and oral (p.o.) administration studies were conducted to calculate the oral bioavailability (BA). For comparison, p.o. studies with therapeutic dose (ThD) levels were also performed. In all studies, blood concentrations of each drug were successfully determined using liquid chromatography–mass spectrometry with the lower limit of quantification of 0.2–2.0 pg/mL. Oral BA of nifedipine in the MD study was approximately 50% and in the same range with that obtained in the ThD study, whereas other two drugs showed significantly lower BA in the MD study, indicating a dose‐dependent absorption. In addition, compared with the ThD study, absorption of nicardipine was delayed in the MD study. As a result, nifedipine was considered to be most promising for oral use. In conclusion, a cassette‐MD clinical study is of advantage for oral drug development that enables to identify the candidate having desired properties for oral use. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:3154–3161, 2015